2007
DOI: 10.7202/032607ar
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Sedimentological Studies on the Wisconsinan Stratigraphy of Southern Ontario

Abstract: ABSTRACTDetailed facies mapping along Lake Erie and Lake Ontario Bluffs, plus other studies illustrate that sedimentological studies, especially those with geomorphic or landform control, have had three main effects on the Wisconsinan stratigraphy of Ontario: (1) improved understanding of depositional processes and environments of several major rock stratigraphic units, without altering the stratigraphic framework, (2) aided correlation of drift sequences, and (3) questioned pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…2) overlies the Scarborough Formation and records the further encroachment of ice into the Ontario basin. Divergent views on the origin of these deposits, i.e., glacial (Karrow 1967;Sharpe and Barnett 1985;Hicock and Dreimanis 1992) sented; however, both interpretations are in agreement regarding the presence of glacial ice well within the Lake Ontario basin. Ice certainly advanced south and west of the Rome outlets (Fig.…”
Section: Quaternary Geologymentioning
confidence: 77%
See 2 more Smart Citations
“…2) overlies the Scarborough Formation and records the further encroachment of ice into the Ontario basin. Divergent views on the origin of these deposits, i.e., glacial (Karrow 1967;Sharpe and Barnett 1985;Hicock and Dreimanis 1992) sented; however, both interpretations are in agreement regarding the presence of glacial ice well within the Lake Ontario basin. Ice certainly advanced south and west of the Rome outlets (Fig.…”
Section: Quaternary Geologymentioning
confidence: 77%
“…Modified from Dreimanis (1992). a drop in base level causing subaerial erosion of the delta surface (Karrow 1967); enhanced scour by fluvial feeder systems and slumps off the delta front during ice advance from the northeast ; or subglacial meltwater erosion (Sharpe and Barnett 1985). Karrow (1974) suggested that fossiliferous gravels (Pottery Road Formation) partially infilling these valleys may be correlative to the St. Pierre beds in the St. Lawrence lowlands.…”
Section: Quaternary Geologymentioning
confidence: 99%
See 1 more Smart Citation
“…comm. cited in Sharpe & Russell ), or between deposition of the NT and the HT, during a period of localized ice withdrawal (White ; Chapman & Putnam ; Sharpe & Barnett ; Karrow ; Slomka ). Areas where the ice re‐advanced over lake sediments deposited during ice withdrawal are recorded by deposition (and streamlining) of fine‐grained HT; areas that remained ice‐covered during the flow switching display multiple bedform populations recorded on the surface of the NT, as no new material was available for incorporation into a younger till sheet.…”
Section: Discussionmentioning
confidence: 99%
“…In places, boulders occurring at the base of the Sunnybrook diamicton are striated on the top surface (Sharpe & Barnett 1985) and in others they appear to be, but may not be, similar to boulders found projecting from melt-out till sequences within Halton (Fig. 18).…”
Section: Summary Of Sedimentary Environmentsmentioning
confidence: 85%